Toxic metals in indoor dust collected from houses included in the “6x60x6” Project (Covilhã, Portugal) during the cooling season - Pastorinho, Ramiro (2016)
We spend more than 90 per cent of our daily lives indoors. Managing the indoor environment so that we feel comfortable and healthy is therefore very important. However, this management is only possible if rigorous data on both construction parameters and indoor environment exists. Moreover, the evolution of construction techniques and materials used modulates both aspects. As a consequence, it is necessary that the information obtained reflects a long period of time. That is the main driver for the project “Six by Sixty by Six” undertaken by the Civil Engineering and Architecture Department and the Faculty of Health Sciences of the University of Beira Interior. Six houses constructed in six different decades (1960’s-2010’s) were surveyed for sixty days regarding a set of parameters (e.g., temperature, humidity, CO2, CO, VOCs). Additionally, dust was collected by the vacuum cleaner bag and was analyzed for specific contaminants. This work presents the results obtained for the toxics metals mercury, arsenic, cadmium, and lead in dust samples. There is no legislation regulating maximum permissible levels for any of the studied metals in dust. A comparison with ”Portaria Nº 1450/2007” which regulates the maximum metal contents in dredged sediment that can be safely deposited in soils (here used as an action threshold) reveals that the values for As in all houses were transcended. For Cd and Hg they were only transcended in one house, whereas for lead all the values were below this threshold. Linear regression with age of construction used as independent variable revealed no relationship between this variable and metal concentrations with the exception of As (R2 adjusted= 0.41). Findings are discussed under the light of potential health outcomes upon the residents.